(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
At the crossroads between Africa, Asia, and Europe, Turkey occupies a prominent position regarding terrestrial mammal interchanges. In stark contrast with a wealth of Late Miocene fossil record, the Early Pliocene interval was virtually undocumented for large mammals in Turkey so far, which made it impossible to characterise their biogeographical affinities in the concerned time interval. In this study, we present the first record of the mammutid proboscidean “Mammut” borsoni in Turkey, found in association with the rhinocerotid Pliorhinus megarhinus, in Lower Pliocene lignite beams at the Tufanbeyli Thermal Power Plant Lignite Operation site, Adana. “Mammut” borsoni spans the Pliocene–Early Pleistocene interval in Eurasia while Pliorhinus megarhinus is a conspicuous element of uppermost Miocene-Pliocene faunas in Western Eurasia and Turkey. This megamammal assemblage represents an important advance in our knowledge of the large mammal faunas of the Early Pliocene of Asia Minor, further attesting to close biogeographic affinities between Anatolia and other circum-Mediterranean regions just after the end-Miocene salinity crisis.